2013
DOI: 10.3810/hp.2013.08.1069
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Venous Thromboembolism Prophylaxis for Hospitalized Medical Patients

Abstract: In the last decade, greater focus has been directed toward venous thromboembolism (VTE) prophylaxis in hospitalized, non-surgical patients. Both deep venous thrombosis and pulmonary embolism are potentially preventable causes of patient morbidity and mortality related to hospitalization. Despite the availability of high-quality, evidence-based guidelines for VTE prevention, there is compelling evidence that many hospitalized patients do not receive appropriate VTE prevention measures. Hospitalists play an impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…1 The Joint Commission and National Quality Forum monitors VTEs as one of its core performance measures, specifically VTE prophylaxis. 2 The occurrence of lower extremity deep vein thrombosis (LEDVT), averaging approximately 187 000 cases per year in the United States, is considered the third most frequent vascular disease after myocardial infarction and stroke. 3,4 Patients with acute LEDVT may have risk factors such as surgery, prolonged length of procedures, weakness or paresis, malignancy, and advanced age.…”
Section: Introductionmentioning
confidence: 99%
“…1 The Joint Commission and National Quality Forum monitors VTEs as one of its core performance measures, specifically VTE prophylaxis. 2 The occurrence of lower extremity deep vein thrombosis (LEDVT), averaging approximately 187 000 cases per year in the United States, is considered the third most frequent vascular disease after myocardial infarction and stroke. 3,4 Patients with acute LEDVT may have risk factors such as surgery, prolonged length of procedures, weakness or paresis, malignancy, and advanced age.…”
Section: Introductionmentioning
confidence: 99%
“…Despite consensus guidelines recommending thromboprophylaxis for at-risk patients in the hospital [ [8] , [9] , [10] ], appropriate thromboprophylaxis remains underutilized or misapplied. Studies suggest that those at the highest risk are inadequately covered and the majority of patients receiving thromboprophylaxis may not truly be at sufficient risk [ [11] , [12] , [13] ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from multiple historical randomized clinical trials and meta-analyses has shown chemoprophylaxis in high-risk hospitalized surgical patients is safe and effective for reducing VTE. [5][6][7][8][9][10] However, evidence may not be broadly adopted, [11][12][13] and population-based studies have shown little decline in either VTE incidence 14 or case fatality. 15,16 Conversely, a large administrative database review showed no correlation between prophylaxis rates and VTE, in part due to surveillance bias.…”
mentioning
confidence: 99%